2018
DOI: 10.1515/geochr-2015-0097
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the vessel lumen area tree-ring parameter of <i>Quercus robur</i> with linear and nonlinear machine learning algorithms

Abstract: Climate-growth relationships in Quercus robur chronologies for vessel lumen area (VLA) from two oak stands (QURO-1 and QURO-2) showed a consistent temperature signal: VLA is highly correlated with mean April temperature and the temperature at the end of the previous growing season. QURO-1 showed significant negative correlations with winter sums of precipitation. Selected climate variables were used as predictors of VLA in a comparison of various linear and nonlinear machine learning methods: Artificial Neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Thus, given that our study occurred in a subtropical area, our focus turned to using machine learning methods. Artificial neural network (ANN) was considered as a better choice for careful assessment of complex climate-growth relationships [20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. However, the learning method process of an ANN is a "black box operation" [51][52][53], meaning that it is sensitive to overfitting and ANNs have difficulty evaluating the contribution of each variable to the results, from a statistical point of view [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given that our study occurred in a subtropical area, our focus turned to using machine learning methods. Artificial neural network (ANN) was considered as a better choice for careful assessment of complex climate-growth relationships [20,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. However, the learning method process of an ANN is a "black box operation" [51][52][53], meaning that it is sensitive to overfitting and ANNs have difficulty evaluating the contribution of each variable to the results, from a statistical point of view [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we did not evaluate the influence of climate metrics on VLAs or specific hydraulic conductivity. Even though many studies have reported tree height as a dominant factor of basipetal widening ( Fajardo et al, 2020 ), some recent studies have highlighted the influence of temperature ( Jevšenak et al, 2018a ) and precipitation ( Castagneri et al, 2017 ; Jevšenak et al, 2018b ) on VLAs and hydraulic conductivity. In addition, climate has an undeniable influence on the tree ring widths of both the studied tree species ( Rybníček et al, 2016 ; Roibu et al, 2020 ), and specifically influences the growth of trees of different dimensions ( Trouillier et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the conduit elements of trees increases ontogenetically with the increasing distance from the stem base to the apex ( Olson et al, 2014 ; Kašpar et al, 2019 ; Fajardo et al, 2020 ). This general pattern is partly influenced by climate (e.g., Fonti et al, 2013 ; Castagneri et al, 2017 ; Jevšenak et al, 2018a , b ) and partly by the formation of reaction wood ( Jourez et al, 2001 ). This reaction wood generally has vessels with smaller lumens ( Tumajer et al, 2015 ) and different density ( Heinrich et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a situation might lead to non‐linear and temporarily unstable relationships between tree growth and climatic factors (Wilmking et al, 2020). Consequently, calibrated climate–growth response functions might not accurately reflect growth variability outside the calibration period, which might reduce the validity of both climate reconstructions and forecast models of forest growth (Jevšenak et al, 2018). This phenomenon, referred to as the “divergence problem” (D'Arrigo et al, 2008) or “non‐stationarity” (Wilmking et al, 2020), is likely widespread and might affect most forest biomes across the globe (Buchwal et al, 2020; Büntgen et al, 2006; Kirdyanov et al, 2020; Wilmking et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, non‐linear process‐based models should be less prone to divergence bias (Kirdyanov et al, 2020; Tolwinski‐Ward et al, 2011). However, a systematic comparison of the predisposition to non‐stationarity of linear versus non‐linear models has so far not been presented (but see Jevšenak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%